1965
DOI: 10.1002/qj.49709138704
|View full text |Cite
|
Sign up to set email alerts
|

Moisture transfer in free and forced convection

Abstract: MR. J. S. SAWYER : As the author remarks, if equality of K , and Kh exists it is to be attributed to the correlation of humidity and density fluctuations in the turbulent flow. Such a correlation must be affected by the nature ofthe evaporation process at the gr0unde.g. whetherthe evaporating areas are warm or cool relative to areas with less evaporation. Does this imply that the ratio of K , and Kh found in any experiments such as those reported by the author will be rather dependent on the evaporative proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1965
1965
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Results of this study suggest that the Monin-Obukhov equations describe satisfactorily the vertical profiles of meteorological parameters above a rough vegetation, and that fluxes of sensible and latent heat above a forest can be obtained from profile measurements only. It is worth mentioning that the value of 1.24 was obtained for the dimensionless heat flux, which is in good agreement with values above surfaces with small roughness obtained by others (Crawford, 1965;Dyer, 1967).…”
Section: Vertical Turbulent Fluxes Above Forestssupporting
confidence: 90%
“…Results of this study suggest that the Monin-Obukhov equations describe satisfactorily the vertical profiles of meteorological parameters above a rough vegetation, and that fluxes of sensible and latent heat above a forest can be obtained from profile measurements only. It is worth mentioning that the value of 1.24 was obtained for the dimensionless heat flux, which is in good agreement with values above surfaces with small roughness obtained by others (Crawford, 1965;Dyer, 1967).…”
Section: Vertical Turbulent Fluxes Above Forestssupporting
confidence: 90%
“…AET measurements were performed using the Bowen ratio energy balance The assumptions made when using the Bowen ratio technique (Peacock and Hess 2004) are: (1) Turbulent transfer coefficients for heat and water vapor are identical. A recent study found that the similarity theory applied in all atmospheric stability situations, thus confirmed earlier work such as Businger et al (1971) and Crawford (1965). McNaughton and Laubach (1998), in their similarity studies, concluded that Bowen ratio technique will be satisfactory except with quite inversions.…”
Section: Methodssupporting
confidence: 72%
“…The experimental results of Crawford (1965), Dyer (1967), and Swinbank and Dyer (1967) indicate that, in the region where the temperature distribution can be represented by Eq. 2 122, H* has a value of about 1 15 to 1.3.…”
Section: Temperature Profiles and Heat Flux Stratified Airmentioning
confidence: 96%